The Role of Enterprise Risk Management as an Intervening Variable in Good Corporate Governance on the Value of Firm in the Banking Sub-Sector - Syahputri, Hilda Mega; Sumani, Sumani; Awwaliyah, Intan Nurul (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
Every business faces inevitable risks, especially amid economic uncertainty and competition. Enterprise Risk Management (ERM) plays a vital role in protecting and enhancing firm value through informed decision-making. Good Corporate Governance (GCG) supports ERM by improving transparency and investor confidence. This study examines the effect of managerial ownership, institutional ownership, independent commissioners, Risk Management Committee (RMC), and auditor reputation on firm value in the banking sector, both directly and through ERM as an intervening variable. Using an explanatory quantitative approach with secondary data from banking companies listed on the Indonesia Stock Exchange (2019–2023), the analysis was conducted using Partial Least Squares (PLS). The results reveal that managerial ownership, institutional ownership, and independent commissioners do not significantly affect firm value. The RMC and auditor reputation (especially from Big Four firms) positively influence ERM implementation, though auditor reputation does not directly affect firm value. However, ERM effectively enhances firm value and mediates the relationship between auditor reputation and firm value. Strengthening a comprehensive ERM framework is essential to improve corporate risk management and firm performance.